Delayed presentation of major complications in patients undergoing cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy following hospital discharge. Issue 3 (31st December 2014) - Bhagwandin, Shanel B.; Naffouje, Samer; Salti, George
<x xml:space="preserve">Abstract</x> Introduction Peritoneal surface malignancy is increasingly treated with cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC). This is associated with potentially high morbidity. We analyzed the incidence of delayed major complications following CRS plus HIPEC. Methods Delayed events were chosen as those which occurred after discharge from the hospital following CRS plus HIPEC and prior to 90 days. Major complications included any adverse event requiring intervention or intensive care unit admission. Results One hundred thirty six patients underwent 140 procedures. Eight patients (5.7%) developed delayed major complications. Complications were pancreatic pseudocyst/pancreatitis (n = 3), abdominal wall dehiscence (n = 2), gastric perforation (n = 1), and ureteral stricture with associated hydronephrosis (n = 2). All of the patients had undergone multivisceral resections. Seven patients achieved complete cytoreduction (cc ≤ 1). Mean peritoneal carcinomatosis index (PCI) was 15.25 ± 5.33 (6–22). Standard of care was met for the management of all the complications and all patients recovered following intervention without any further morbidity or mortality. Conclusion There is a lack of report of the delayed major complications in patients undergoing CRS plus HIPEC in the literature. Awareness should be raised among health care providers regarding possible occurrence of such late complications given that many patients undergo CRS plus HIPEC remotely from their localities. J. Surg. Oncol. 2015 111:324–327. © 2014 Wiley Periodicals, Inc.